Sex Differences in Metabolism of Trichloroethylene and Trichloroethanol in Guinea Pigs. Issue 6 (19th March 2014) - Hibino, Yui; Wang, Hailan; Naito, Hisao; Zhao, Na; Wang, Dong; Jia, Xiaofang; Li, Hongling; Song, Xiangrong; Liu, Lili; Huang, Yongshun; Ito, Yuki; Huang, Hanlin; et al.
Abstract : Sex Differences in Metabolism of Trichloroethylene and Trichloroethanol in Guinea Pigs: Yui HIBINO, et al . Department of Occupational and Environmental Health, Nagoya University Graduate School of Medicine— Objectives: Trichloroethylene (TRI) has the potential to cause generalized dermatitis complicated with hepatitis. The guinea pig maximization test (GPMT) also suggests that both TRI and its metabolite trichloroethanol (TCE) exhibit immunogenicity and possible sex differences in guinea pigs. However, TRI and TCE metabolisms in guinea pigs have not been elucidated in detail. The first issue to clarify may be the sex differences in relation to the immunogenicity. Methods: We collected urine from Hartley male and female guinea pigs 24 hours after intracutaneous injection of TRI, TCE or trichloroacetic acid (TCA) during a GPMT and measured the urinary metabolites by gas chromatography‐mass spectrometry. Results: After TRI treatment, the amount of TCA was significantly greater in females than males, while there was no sex difference in the total amount (TCA + TCE). TCA was only detected in urine after TCA treatment. Interestingly, not only TCE but also TCA was detected in urine of both sexes after TCE treatment, and the amount of TCA was also greater in females than males. An additional experiment showed that TCE treatment did not result in the detection of urinary TCA in cytochrome P450 (CYP)2E1‐null mice but did in wild‐type mice, suggesting the involvement of CYP2E1 in the metabolism from TCE to TCA. The constitutive expression of CYP2E1 in the liver of guinea pigs was greater in females than males. Conclusions: The sex difference in urinary TCA excretion after TRI and TCE treatments may be due to variation of the constitutive expression of CYP2E1.